Financial Well-Being Stratification among Urban Households: A Multinomial Logit Analysis of Digital Payments, Saving Behavior, and Credit Access - Dhidhin Noer Ady Rahmanto; Ragil Satria Wicaksana; Ratih Purbowisanti (CV. Civiliza Publishing, 2026)
Rising global economic uncertainty in the aftermath of the COVID-19 pandemic has underscored the importance of household financial well-being (FWB) as a key pillar of economic resilience, particularly in urban settings. This study analyzes how digital payment adoption, saving behavior, and access to credit contribute to the stratification of FWB among urban households in Indonesia. The analysis uses microdata from the 2017 Survey on Financial Inclusion and Access (SOFIA), focusing on a sub-sample of 2,368 urban households aged 19–40 years across four provinces. FWB is constructed as an ordered categorical variable with four levels Low, Medium, High, and Very High based on multiple indicators of financial capability and access. A multinomial logit model is employed, with results interpreted using Average Marginal Effects (AMEs). The findings indicate that regular saving behavior and access to formal credit are the most consistent determinants of upward mobility across FWB categories. Regular saving significantly reduces the likelihood of being in the Low and Medium FWB categories and substantially increases the probability of attaining High FWB. Access to credit strongly increases the likelihood of reaching the Very High FWB category. The results suggest that financial inclusion in urban contexts should be understood as a combination of disciplined financial behavior and deeper engagement with formal financial services